Tissue‐Specific Distribution of Sphingomyelin Species in Pork Chop Revealed by Matrix‐Assisted Laser Desorption/Ionization–Imaging Mass Spectrometry. Issue 7 (17th June 2019) - Enomoto, Hirofumi; Takeda, Shiro; Hatta, Hajime; Zaima, Nobuhiro
Abstract : Abstract: Sphingomyelin (SM) species are major sphingolipids in pork meat that affect quality parameters, such as health benefits due to their protective properties against chronic diseases; however, their spatial distribution remains unclear. We used matrix‐assisted laser desorption/ionization (MALDI)–imaging mass spectrometry (IMS) to investigate the distribution and composition of SM species in pork chop consisting of longissimus thoracis et lumborum muscle (loin), intermuscular fat tissue, transparent tissue, and spinalis muscle. Four SM species were identified by liquid chromatography–electrospray ionization–tandem MS (MS/MS) and MALDI–MS/MS and visualized using MALDI–IMS. SM species containing stearic acid were predominantly distributed in the loin and spinalis muscle, whereas SM species containing palmitic, lignoceric, and nervonic acids were predominantly distributed in transparent tissue. These results indicated that the distribution of SM species differed among the pork tissues, depending on the tissue‐specific fatty acid composition. The total amount including all identified SM species was higher in the loin than in spinalis muscle. Pork is reportedly associated with increased risk for chronic diseases due to the high amount of heme iron. From the observation of color, the amount of heme iron was lower in loin than in spinalis muscle. Thus, the degree of risk for chronic diseases might be lower in the loin than in spinalis muscle. This is the first report on the tissue‐specific distribution of SM species in meat at a microscopic resolution using IMS. MALDI–IMS analysis may be useful in assessing the association between SM species and quality parameters of pork meat. Practical Application: Sphingomyelin (SM) species are major sphingolipids in pork meat. SM species affect quality parameters such as health benefits due to their protective properties against colon cancer and atherosclerosis. Matrix‐assisted laser desorption/ionization–imaging mass spectrometry analysis combined with liquid chromatography–electrospray ionization‐tandem mass spectrometry is a suitable method to directly investigate the distribution and composition of SM species at microscopic level among different tissues of pork meat. Therefore, this method is useful to assess the SM species‐induced health effect of different tissues of pork meat.